Non-additive phenotypic and transcriptomic inheritance in a citrus allotetraploid somatic hybrid between C. reticulata and C. limon: the case of pulp carotenoid biosynthesis pathway - Bassene, Jean Baptiste; Froelicher, Yann; Dhuique-Mayer, Claudie; Mouhaya, Waffa; Ferrer, Rosa M.; Ancillo, Gema; Morillon, Raphael; Navarro, Luis; Ollitrault, Patrick (2017)
Allopolyploidy is known to induce novel patterns of gene expression and often gives rise to new phenotypes. Here we report on the first attempt to relate phenotypic inheritance in an allotetraploid somatic hybrid with gene expression. Carotenoid compounds in the fruit pulp of the two parental species and the hybrid were evaluated quantitatively by HPLC. Only very low levels of beta-carotene and beta-cryptoxanthin were observed in Citrus limon, while beta-cryptoxanthin was a major component of C. reticulata, which also displayed high levels of phytoene, phytofluene, beta-carotene, lutein, zeaxantin and violaxanthin. Total carotenoid content in mandarin juice sacs was 60 times greater than that in lemon. The allotetraploid hybrid produced all the same compounds as mandarin but at very low levels. Transgressive concentration of abscisic acid (ABA) was observed in the somatic hybrid. Real-time RT-PCR of total RNA from juice sacs was used to study expression of seven genes (CitDxs, CitPsy, CitPds, CitZds, CitLcy-b, CitChx-b, and CitZep) of the carotenoid biosynthetic pathway and two genes (CitNced1 and CitNced2) involved in abscisic acid synthesis from carotenoid. Gene expression was significantly higher for mandarin than lemon for seven of the nine genes analyzed. Lemon under expression was partially dominant in the somatic hybrid for three upstream steps of the biosynthetic pathway, particularly for CitDxs. Transgressive over expression was observed for the two CitNced genes. A limitation of the upstream steps of the pathway and a downstream higher consumption of carotenoids may explain the phenotype of the somatic hybrid.